Attitudes of Parents of Children with Typical Development Towards Inclusion of Children with Developmental Disabilities in Primary Schools in the Municipality of Gračanica - Kompirović, Tatjana P.; Radojević, Tatjana S.; Pavlović, Marija D. (Collection of Papers of the Faculty of Philosophy in Priština, 2023)
The paper discusses the basic constructive and pedagogical aspects related to the attitudes of parents of children with typical development towards inclusion and the importance of including children with developmental disabilities in the regular education system. Inclusion is a process that promotes universal acceptance and a sense of belonging for all students, not just the physical inclusion of children with disabilities in the regular education system. In order for a child with developmental disabilities to be included in the regular education system as successfully as possible, synchronized cooperation between the school, on the one hand, and the parents of children with developmental disabilities and the parents of children with typical development, on the other hand, is necessary. Taking this into account, the importance of the attitudes of parents of typically developing children towards inclusion is clear. Accordingly, the aim of the paper was to theoretically and empirically determine and explain the attitudes of parents of children with typical development towards inclusion and the importance of including children with developmental disabilities in the regular education system. The research sample consisted of parents of children with typical development (N = 205) from Kosovo and Metohija, specifically the municipality of Gračanica. The data were processed with descriptive statistics, based on the questionnaire which was constructed for the purposes of the research. The results of the research show that in the examined sample of parents of children with typical development, there are two polarities of attitudes towards inclusion and the inclusion of children with developmental disabilities in regular education, which shows that it is necessary to constantly work on raising awareness of public opinion about the importance of inclusion and its importance for all children, but also on ensuring and improving the conditions for its full implementation.